Three distinct activities possibly involved in mRNA splicing are found in a nuclear fraction lacking U1 and U2 RNA. - Mayeda, A (1986)
A nuclear extract from HeLa cells was fractionated by DEAE-Sepharose chromatography, and the fractions were assayed for the binding activity for a small RNA transcript carrying a splice junction or branch point sequence. The binding activity for the RNA carrying a 5' splice junction was localized in the small nuclear ribonucleoprotein (snRNP) fraction together with binding activity for the RNA carrying a 3' splice junction or branch point sequence. However, stronger binding activities for the 3' splice junction RNA and for the branch point RNA were discovered in the flow-through fraction where no small nuclear RNA were detected. When the flow-through fraction was added to purified U1 ribonucleoprotein, the binding activity for the 5' splice junction RNA was markedly enhanced. We propose that the factors responsible for the three types of activities found in the flow-through fraction play a role in the splicing of mRNA precursor.